Healing Mechanism of Ruptured Fetal Membrane - Mogami, Haruta; Word, R. Ann (Frontiers in Physiology, 2020)
Preterm premature rupture of membranes (pPROM) typically leads to spontaneous preterm birth within several days. In a few rare cases, however, amniotic fluid leakage ceases, amniotic fluid volume is restored and pregnancy continues until term. Amnion, the collagen-rich layer that forms the load-bearing structure of the fetal membrane, has regenerative capacity and has been used clinically to aid in the healing of various wounds including burns, diabetic ulcers, and corneal injuries. In the healing process of ruptured fetal membranes, amnion epithelial cells seem to play a major role with assistance from innate immunity. In a mouse model of sterile pPROM, macrophages are recruited to the injured site. Well-organized and localized inflammatory responses cause epithelial mesenchymal transition of amnion epithelial cells which accelerates cell migration and healing of the amnion. Research on amnion regeneration is expected to provide insight into potential treatment strategies for pPROM.